Developing country and industry materiality assessments to increase sustainable FDI - Nitesh Dullabh (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
An alignment between country-led ESG indicators and industry materiality assessment topics that coincide with MNEs' specific ESG-related indicators drive impactful, sustainable FDI. This Perspective suggests the creation of country and industry materiality assessments to promote sustainable FDI through an environmental, social, and governance (ESG) lens.
Keywords: 330